El crédito del bono de desarrollo humano en los emprendimientos de los beneficiarios del cantón Gonzalo Pizarro, provincia de Sucumbíos periodo 2017 – 2018 - Francisca Marina, Chucuri Mero (2020)
The research`s topic is “The Credit of the Human Development Bond in the Entrepreneurship of the beneficiaries of the Gonzalo Pizarro, Sucumbíos province period 2017-2018", through which it allowed to have a broad knowledge and real about how human development credit is contributing to the businesses of the Canton. The research is segmented by chapters, the first chapter encompasses everything related to the problem statement and the objectives, which has allowed the development of the research to be correct. It also details the different problems that arise around the exposed problem. In the chapter we have everything related to the state of the art and to the theoretical foundation, that is to say, several quotes from authors who have carried out research on the subject of study have been exposed, which has allowed us to have a better vision when analyzing the specialized literature on the subject, also in this chapter all the information of the two variables that are the object of study is detailed. In the third chapter we have all the methodology, here the method, type, research design that was used throughout the investigation is detailed, in addition to the tools that were used in the collection of information, also the procedure that was carried out to process the information in order to make an analysis and interpretation understandable. Finally, in the fourth chapter, once the corresponding information is processed, the respective conclusions and recommendations that have been obtained in the word are issued, keeping the relationship with the objectives that have been previously exposed.